Načrtovanje sestave mešanice zemljine za uporabo v nenosilnih predelnih butanih stenah - Smolar, Jasna (Gradbeni vestnik, 2025)
Soil, similar to wood and stone, is one of the oldest construction materials, locally available and environmentally sustainable. In recent years, within the broader framework of the circular economy and sustainable construction practices, interest in rammed earth has grown. However, its wider implementation in Slovenia is still limited by the absence of valid national standards and technical guidelines prescribing testing methods, required material properties, and construction rules. The first part of the article introduces the concept of using rammed earth in contemporary built environments and summarizes key requirements from selected international technical guidelines for mixture design. The second part presents geotechnical laboratory tests performed to develop mixtures suitable for non-structural rammed earth walls, comparing the obtained properties with the criteria defined in foreign standards. The third part examines the mechanical properties of t wo non-structural test walls built from the selected mixture. The laboratory results are promising, demonstrating that standard geotechnical procedures can be effectively applied to mixture design and to the initial assessment of rammed earth characteristics. The achieved compressive strength of the compacted mixture is shown to depend mainly on particle size distribution and on ensuring appropriate moisture levels at the time of compaction. Compressive testing of the walls indicated relatively high compressive strength but also revealed an unfavourable failure mechanism. Addressing this behaviour in future research will likely require modifications to the mixture, such as the incorporation of natural fibres. To support systematic mixture design and encourage broader use of rammed earth construction in Slovenia, the development of national technical guidelines is essential. These guidelines should harmonize with existing international standards while taking into account local conditions (material availability, ...).
Keywords: butana zemljina; co workability; compaction; compressive strength; laboratorijske mehanske preiskave; laboratory mechanical testing; načrtovanje mešanice; nenosilna stena; non-structural wall; rammed earth; soil mixture design; tlačna trdnost; vgradljivost; zgoščanje